Community Structure of Coral Reef at Pasir Putih Beach In Situbondo East Java, Indonesia - Khusnah, Asmaul; Retnaningdyah, Catur; Kurniawan, Nia (Journal of Indonesian Tourism and Development Studies, 2019)
Pasir putih beach of Situbondo has coral reefs as the potential of underwater beauty. The purpose of this study is to evaluate the structure of coral reef community in Pasir putih beach. This study was taken place at four sites namely; Batu lawang, Teluk pelita, Karang mayit, and Karang pon-pon. Method used was Ex Post Facto using belt transect sampling technique with size 1x1m and length 30m and 11 times repetition. The observed physic-chemistry parameters are temperature, salinity, conductivity, pH, turbidity, DO, nitrate, and orthophosphate. The results showed that the four sites almost have the same conditions. Batu Lawang location is dominated by Porites mayeri (Poritidae) which is vulnerable to severe conditions. The second location (Teluk pelita) has a high index value of diversity. The third location (Karang Mayit) is dominated by Poritidae family. The fourth location (Karang Pon-pon) is dominated by the Acroporidae family which is a clear water indicator and has a fast growth rate. However, in the fourth location, the sedimentation is quite high compared to other sites. The value of abiotic factor in the Pasir putih beaches of Situbondo has a relatively normal value, the pH of value from 7.55 to 7.56, temperature 29.99°C to 30.4°C, salinity 32.33 to 32.66 ‰, conductivity 37.8 to 40.2 µS.cm-1, DO 7.73 to 10 ppm, turbidity 0.57-1.56 NTU, nitrate from 0.32-0.1 mg.L-1 and orthophosphate 0.02 to 0.54 mg.L-1, the water in Pasir Putih Situbondo was still suitable for support the growth of coral reefs. Keywords: Coral Reefs, Community Structures, Pasir putih Beach.